Die Preußische Katasteraufnahme im Herzogtum Kleve der Jahre 1731-38 - Aymans, Gerhard (ERDKUNDE, 1986)
The space covered by hand-drawn maps preserved in archives is generally not known. To make this information available it is suggested that archives extent the listing of such maps from record books to record maps, i.e. to small scale contemporary maps in which the hand-drawn historical maps are to be depicted to scale. This space oriented procedure is particularly desirable in the case of sets of complementary maps of larger regions or territories, since they are rarely preserved in a single archive,but scattered in many. The essay introduces the maps of the so-called Cleves cadastral survey carried out by Prussian engineer officers in the former Dukedom of Cleves in 1731-38. More than a thousand of these maps are known to have survived, and more than a hundred may still be found in some of the minor archives both in Germany and in the Netherlands. They deserve our attention first of all because of their technical qualities. The maps have a scale of 1:2041,5, and the very best differ as little as 0,04% from this scale. Their content, however, is not less reliable, for the allotments presented, down to the smallest garden of a few square feet, were measured, numbered and designated in the presence of the local jurors and of experts put on oath for the purpose. A number of these maps, 37 altogether, cartographically reduced and joined together into a map of the scale 1:10.000, depict the land use of two of the former Cleves communities around 1734 (See supplement map). The reliability of this map is such that it can be used as a safe base for the reconstruction of former states of the region. About 40 years later, in 1775, a land development scheme ordered by the Prussian state changed the surface of this region considerably and the dissolution of the monastries brought about by the French Empire in 1802 added to these changes. The maps of the Cleves cadastral survey of 1731-38 are, therefore, very much superior to all later maps as far as geographical studies into the past of this region is concerned.